STUDENTS’ CULTURAL AWARENESS LEVEL AND THEIR TECHNIQUES FOR INCORPORATING TARGET CULTURAL CONTENT INTO ENGLISH LANGUAGE TEACHING IN ENGLISH TEACHER EDUCATION DEPARTMENT OF UIN SUNAN AMPEL SURABAYA - Maghfirotillah, Qori’ah (IJET (Indonesian Journal of English Teaching), 2016)
Having cultural awareness deals much more with ones’ ability to face global interaction and to communicate appropriately, and thus, is crutial for students taking micro-teaching class of ETED UIN Surabaya as English teacher candidates. To gain meaningful English teaching, ETED students need to highlight that language learning without involving any cultural contents means nothing. This paper is a literature review of the bigger study which aims to examine the level of Students’ cultural awareness in micro teaching class of English Teacher Education Department and the strategies that are used by students of micro teaching class to incorporate cultural aspect into their English language teaching.